Prevalence of Post COVID 19 Cough One Year After SARS CoV 2 Infection: A Multicenter Study - Fernández de las Peñas, César; Guijarro, Carlos; Plaza Canteli, Susana; Hernández Barrera, Valentín; Torres Macho, Juan (My University, 2021)
This multicenter study presents prevalence data and associated risk factors of post-COVID-19 cough one year after hospital discharge in COVID-19 survivors. Individuals recovered from COVID-19 at three public hospitals in Madrid (Spain) were scheduled for a telephonic interview. They were systematically asked about the presence of respiratory symptoms, e.g., fatigue, dyspnea, chest pain, and cough after hospital discharge. Clinical and hospitalization data were collected from hospital records. Overall, 1,950 patients (47% women, mean age:61, SD:16 years) were assessed at 11.2 months (SD 0.5) after hospital discharge. Just 367 (18.8%) were completely free of any respiratory post-COVID -19 symptom. The prevalence of long-term cough, chest pain, dyspnea, and fatigue was 2.5%, 6.5%, 23.3%, and 61.2%, respectively. Clinical and hospitalization factors were not associated with long-term post-COVID-19 cough. In conclusion, the prevalence of post-COVID-19 cough one year after SARS-CoV-2 infection was 2.5% in subjects who had survived hospitalization for COVID-19. No clear risk factor associated to long-term post-COVID-19 cough was identified. Keywords COVID-19 · Cough · Persistent · Symptoms · Risk factors